THU0419 BIOLOGICS IN THE TREATMENT OF CALCIUM PYROPHOSPHATE DEPOSITION DISEASE. A SYSTEMATIC LITERATURE REVIEW. (2nd June 2020) - Cipolletta, E.; DI Matteo, A.; Scanu, A.; Isidori, M.; DI Battista, J.; Punzi, L.; Grassi, W.; Filippucci, E.
Abstract : Background: Only few case reports and case series have analysed the efficacy of IL-1 inhibitors in the treatment of calcium pyrophosphate deposition disease (CPPD), reporting conflicting results. Objectives: The main aim of this systematic literature review (SLR) was to summarize the evidence in the use of biological therapies in CPPD. Methods: PRISMA-IPD guidelines were used for this review. Published articles reporting the use of TNFα and/or IL-1 inhibitors in the treatment of CPPD were reviewed. We performed a SLR using PubMed, Embase and Cochrane databases. The search resulted in 83 articles; 11 were further evaluated in the SLR. Results: Seventy-six patients were included: 2 received infliximab, whereas 74 anakinra. The main data of included studies are reported in table 1 . Sixty-seven (88.2%) patients presented with an acute CPPD (mean disease duration: 2.7±6.9 months; polyarticular involvement in 61.2%, oligoarticular in 31.3% and monoarticular in 7.5%), whereas 9 (11.8%) patients with a chronic CPPD (mean disease duration: 130.1±133.6 months; polyarticular involvement in 66.7% and oligoarticular in 33.3%). Anakinra was used in refractory disease (85.1%) or in patients with contraindications to standard treatments such as colchicine, oral glucocorticoids and/or non-steroidal anti-inflammatory drugs (23.0%). Clinical response to anakinra was reported in table 2 . Duration of anakinra treatment prior to complete resolution of symptoms was associated with the clinical phenotype of chronic CPPD (Rpb: 0.67, p<0.01) and with disease duration (R: 0.49, p<0.01). In 47 out of 57 (82.5%) responders, complete resolution of symptoms was observed within 4 days after the first injection of anakinra. Adverse events were reported in 4.1% of the cases: local skin reaction at the injection site, skin rash on the back and bacterial pneumonia. Conclusion: This SLR provides evidence in favour of the use of anakinra as a therapeutic option in patients with CPPD, especially in acute refractory CPPD or when standard treatments are contraindicated. Disclosure of Interests: Edoardo Cipolletta: None declared, Andrea Di Matteo Grant/research support from: the publication was conducted while Dr. Di Matteo was an ARTICULUM fellow, Anna Scanu: None declared, Martina Isidori: None declared, Jacopo Di Battista: None declared, Leonardo Punzi: None declared, Walter Grassi Speakers bureau: Prof. Grassi reports personal fees from AbbVie, personal fees from Celgene, personal fees from Grünenthal, personal fees from Pfizer, personal fees from Union Chimique Belge Pharma, outside the submitted work., Emilio Filippucci Speakers bureau: Dr. Filippucci reports personal fees from AbbVie, personal fees from Bristol-Myers Squibb, personal fees from Celgene, personal fees from Roche, personal fees from Union Chimique Belge Pharma, personal fees from Pfizer, outside the submitted work.